The Impact of Welfare Benefit Levels and Tax Rates on the Labor Supply of Poor Women - Meyer, Jack A. (The Review of Economics and Statistics, 1975)
The principal problem with previous estimates of the effect of welfare programs on labor supply' is that the specification of the labor supply equation misrepresents the intercept and slope of the budget line for low-income individuals. Labor supply has typically been posited to be a function of the market wage rate unadjusted for the welfare tax rate and other income2 including actual welfare benefits.